2019
DOI: 10.1590/s0102-053620190215
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus sources associated with organic compound in broccoli production and soil chemical attributes

Abstract: Phosphorus is a finite natural resource and the use of gradual-release phosphate sources, associated with an organic compound may favor a more rational use of this nutrient, since organic matter protects P from soil fixation. The aim of this study was to evaluate the effect of phosphorus sources application, associated with organic compound at planting, on single inflorescence type broccoli production and soil chemical properties at the end of the cycle. Eight treatments were evaluated, in a 4 x 2 factorial sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…However, the combination of inorganic fertilizer at intermediate dose (30 kg ha -1 of N) with organic fertilizer had the same effect of high mineral N dose (60 kg ha -1 ). Also, Cardoso et al (2019) found a positive interaction when combining organic composts with mineral fertilizer, denoting their synergistic effect. In our work, the combination of organic PK and mineral N resulted in higher green mass than only organic source, but lower than only mineral sources.…”
Section: Sourcementioning
confidence: 92%
See 1 more Smart Citation
“…However, the combination of inorganic fertilizer at intermediate dose (30 kg ha -1 of N) with organic fertilizer had the same effect of high mineral N dose (60 kg ha -1 ). Also, Cardoso et al (2019) found a positive interaction when combining organic composts with mineral fertilizer, denoting their synergistic effect. In our work, the combination of organic PK and mineral N resulted in higher green mass than only organic source, but lower than only mineral sources.…”
Section: Sourcementioning
confidence: 92%
“…Ouda and Mahadeen (2008) found that the application of organic manure at 80 or 60 t ha -1 increased soil organic matter content and that mineral fertilizer did not have an effect on organic matter content. Yet, Cardoso et al (2019) found that the application of organic compost in broccoli raised pH, in addition to increasing P, K and Ca contents. Chivenge et al (2011) in a meta-analysis to evaluate the effects of organic, mineral and combined N sources on maize, found that the residual soil organic carbon (SOC) was 17% and 12% higher when organic and combined organic and mineral sources were used, respectively, compared to the control (no fertilization).…”
Section: Sourcementioning
confidence: 99%
“…Phosphorus is of great importance in plant development, acting in photosynthesis, respiration, energy storage and transfer, cell division, among other processes, and its presence in adequate levels in the soil solution enhances the production of vegetables (Matos et al, 2016;Cardoso et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, in areas of intensive cultivation of vegetables it is common to find high levels of P (Cecílio Filho et al, 2015) and even so to carry out fertilization with this nutrient. Since phosphorus is a natural and finite resource, excessive use is not sustainable and, therefore, studies on optimizing its use are necessary to achieve sustainable agriculture (Cardoso et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The use of natural phosphates has increased because they are products cheaper than inorganic ones and have agronomic efficiency, providing the nutrient along the cycle, promoting a high yield, and, depending on the source, can be used both in conventional and organic systems (Cardoso et al 2019).…”
mentioning
confidence: 99%